The Moderating Role of HR Service Quality Between e-HRM and Employee Performance - Ris Akril Nurimansjah; Nurjannah Nurjannah; Munawir Munawir; Jafar Basalamah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The objective of this research is to investigate the relationship between e-HRM implementation and employee performance in organizations that use e-HRM, both directly and indirectly mediated by HR service Quality. Using variant-based structural equation (SEM) modeling techniques or partial least squares regression, this research examined the direct relationship between e-HRM and performance, as well as relationships moderated by HR service quality (PLS). Based on the findings, e-HRM has a positive and significant impact on employee performance. Our results additionally highlight the significance of designing and implementing e-HRM so that managers can support the organization's workflow and employees can perform more efficient HR and non-HR tasks. Current research has revealed an emerging relationship between E-HRM, but it has only examined the potential impact of E-HRM. This research also contributes to the e-HRM literature by identifying how e-HRM can improve performance by perceiving the quality of HR services.